Gene eating : the science of obesity and the truth about dieting - Yeo, Giles (Pegasus Books, 2019)
In an age of misinformation and pseudo-science, the world is getting fatter and the diet makers are getting richer. So how do we break this cycle that<U+2019>s literally killing us all? Drawing on the very latest science and his own genetic research at the University of Cambridge, Dr. Giles Yeo has written the seminal “anti-diet” diet book. Exploring the history of our food, debunking marketing nonsense, detoxifying diet advice, and confronting the advocates of clean eating, Giles translates his pioneering research into an engaging, must-read study of the human appetite. In a post-truth world, Gene Eating cuts straight to the data-driven facts. Only by understanding the physiology of our bodies, their hormonal functions, and their caloric needs can we overcome the mis- information of modern dieting trends, empower ourselves to make better decisions, and achieve healthy relationships with food, our bodies, and our weight.